Pelatihan Public Speaking Berbahasa Inggris Menggunakan Media Pop-Up untuk Remaja di Kabupaten Brebes - Elinda Umisara Umisara; Yunika Purwanti Purwanti; Irfan Fauzi Fauzi; Indra Maulana Maulana; Muhamad Toha Toha (LPPM Universitas Harapan Bangsa Purwokerto, 2023)
The English public speaking training using pop-up media for teens in Brebes district is a program designed to improve the public speaking skills of teens. This training will use pop-up media as an engaging and interactive learning aid. The goal of this training is to provide an understanding of good public speaking techniques and to increase the confidence of teens in speaking in public. In addition, the training also give teens the opportunity to practice and apply the techniques they have learned in real-world situations. The methods used in this training are lecture, discussion, and public speaking practice. Pop-up media used as a visual aid to make the training materials more interesting and easier to understand. The training conducted for 6 sessions with a total of 11 participants, the teenager from Brebes District with various ability in English. The training conducted by experienced lecturers from various faculties as facilitator in the field of public speaking and the English language and the results of the training will be measured through oral and written evaluations before and after the training. A learning community of English language will be formed as an effort to support the sustainability of the training and develop the potential of the participants involved.